Whispering Gallery Mode Resonances from Ge Micro-Disks on Suspended Beams - Al-Attili, Abdelrahman Zaher; Kako, Satoshi; Husain, Muhammad K.; Gardes, Frederic Y.; Higashitarumizu, Naoki; Iwamoto, Satoshi; Arakawa, Yasuhiko; Ishikawa, Yasuhiko; Arimoto, Hideo; Oda, Katsuya; Ido, Tatemi; Saito, Shinichi (Frontiers in Materials, 2015)
Ge is considered to be one of the most promising materials for realizing full monolithic integration of a light source on a silicon (Si) photonic chip. Tensile-strain is required to convert Ge into an optical gain material and to reduce the pumping required for population inversion. Several methods of strain application to Ge are proposed in literature, of which the use of free-standing beams fabricated by micro-electro-mechanical systems (MEMS) processes are capable of delivering very high strain values. However, it is challenging to make an optical cavity within free-standing Ge beams, and here, we demonstrate the fabrication of a simple cavity while imposing tensile strain by suspension using Ge-On-Insulator (GOI) wafers. Ge micro-disks are made on top of suspended SiO_2 beams by partially removing the supporting Si substrate. According to Raman spectroscopy, a slight tensile strain was applied to the Ge disks through the bending of the SiO2 beams. Whispering-Gallery-Mode (WGM) resonances were observed from a disk with a diameter of 3um, consistent with the finite-domain time-difference simulations. The quality (Q) factor was 192, and upon increasing the pumping power, the Q-factor was degraded due to the red-shift of Ge direct-gap absorption edge caused by heating.